2019
DOI: 10.1111/pedi.12868
|View full text |Cite
|
Sign up to set email alerts
|

KLF11 variant in a family clinically diagnosed with early childhood‐onset type 1B diabetes

Abstract: KLF11 is the causative gene for maturity‐onset diabetes of the young 7 (MODY7). KLF11 regulates insulin gene expression through binding to the GC box in the promoter. To date, only two KLF11 mutations have been identified in three families with early‐onset type 2 diabetes. Here, we report a novel KLF11 variant associated with early childhood‐onset type 1B diabetes. The proband and his younger sister exhibited hyperglycemia at age 1 year, and their mother developed diabetes at age 4 years. These three individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al 51 , Zhang et al 52 , Hartz et al 53 , Słomiński et al 54 , Johansson et al 55 , Pan et al 56 , Lopez-Sanz et al 57 , Grant 58 , Słomiński et al 59 , Galán et al 60 , Jordan et al 61 , Winkler et al 62 , Yip et al 63 , Crookshank et al 64 , Lempainen et al 65 , Qu and Polychronakos 66 , Morrison et al 67 , Zhang et al 68 , Gerlinger-Romero et al 69 , Belanger et al 70 , Dieter et al 71 , Wanic et al 72 , Ushijima Wanic et al 73 , Guo et al 74 , Davis et al 75 , Elbarbary et al 76 , Villasenor et al 77 , Zhang et al 78 , Lee et al 79 , Zhi et al 80 , Li Calzi et al 81 , Sebastiani et al 82 , Cherney et al 83 , Doggrell 84 and Yanagihara et al 85 studied the clinical and prognostic values of FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N -methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 in patients with T1DM. Vassilev et al 86 , Qin et al 87 , Ma et al 88 , West et al 89 , Hoffmann et al 90 , Deary et al 91 , Belangero et al 92 , Jung et al 93 , Tang et al 94 , Goodier et al 95 , Petyuk et al 96 , Roux et al 97 , Castrogiovanni et al…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al 51 , Zhang et al 52 , Hartz et al 53 , Słomiński et al 54 , Johansson et al 55 , Pan et al 56 , Lopez-Sanz et al 57 , Grant 58 , Słomiński et al 59 , Galán et al 60 , Jordan et al 61 , Winkler et al 62 , Yip et al 63 , Crookshank et al 64 , Lempainen et al 65 , Qu and Polychronakos 66 , Morrison et al 67 , Zhang et al 68 , Gerlinger-Romero et al 69 , Belanger et al 70 , Dieter et al 71 , Wanic et al 72 , Ushijima Wanic et al 73 , Guo et al 74 , Davis et al 75 , Elbarbary et al 76 , Villasenor et al 77 , Zhang et al 78 , Lee et al 79 , Zhi et al 80 , Li Calzi et al 81 , Sebastiani et al 82 , Cherney et al 83 , Doggrell 84 and Yanagihara et al 85 studied the clinical and prognostic values of FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N -methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 in patients with T1DM. Vassilev et al 86 , Qin et al 87 , Ma et al 88 , West et al 89 , Hoffmann et al 90 , Deary et al 91 , Belangero et al 92 , Jung et al 93 , Tang et al 94 , Goodier et al 95 , Petyuk et al 96 , Roux et al 97 , Castrogiovanni et al…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Sox17, a known target of HIF1A and regulator of insulin secretion, was upregulated in the AQ-islets (27,28). Another regulator of insulin gene transcription, Klf11, as well as transcription factors important for β-cell development and function, Nkx2-2 and Nkx6-1, had similar increased expression in islets from AQ-treated pups (29)(30)(31)(32). FoxM1, a transcription factor essential for β-cell postnatal proliferation, was downregulated in the AQ-islets (33) (Fig.…”
Section: Activation Of Hif1a By Aq Leads To Changes In the Whole Islet Transcriptomementioning
confidence: 89%
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al [52], Zhang et al [53], Hartz et al [54], Słomiń ki et al [55], Johansson et al [56], sPan et al [57], Lopez-Sanz et al [58], Grant, [59], Słomiń i et al [60], Galán et al sk [61], Jordan et al [62], Winkler et al [63], Yip et al [64], Crookshank et al [65], Lempainen et al [66], Qu and Polychronakos, [67], Morrison et al [68], Zhang et al [69], Gerlinger-Romero et al [70], Belanger et al [71], Dieter et al [72], Wanic et al [73], Ushijima Wanic et al [74], Guo et al [75], Davis et al [76], Elbarbary et al [77], Villasenor et al [78], Zhang et al [79], Lee et al [80], Zhi et al [81], Li Calzi et al [82], Sebastiani et al [83], Cherney et al [84], Doggrell, [85] and Yanagihara et al [86] found that FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N-methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 are involved in the progression of T1DM. Vassilev et al [87], Qin et al [88], Ma et al [89], West et al [90], Hoffmann et al [91], Deary et al [92], Belangero et al [93], Jung et al [94], Tang et al [95], Goodier et al [96], Petyuk et al [97], Roux et al [98], Castrogiovanni et al [99], Suleiman et al [100], Haack et al [101], Kwiatkowski et al [102], Pinacho et al [103], Luo et al [104], He et al [105], Moudi et al [106], Thevenon et al [107], Li et al [108], Reitz et al [109], Jenkins and Escayg [110], Letronne et al [111], Ma et al [112<...>…”
Section: Discussionmentioning
confidence: 99%